Prom - Bell, Martin (Los Angeles : J. Paul Getty Museum, 2012)
Features interviews with the high school students, who were photographed by Mary Ellen Mark at their proms at thirteen schools across the United States.
Keywords: High school students -- Interviews; High school students; Proms -- United States